If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -2r = 3r + 11 Reorder the terms: 16 + -2r = 11 + 3r Solving 16 + -2r = 11 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 16 + -2r + -3r = 11 + 3r + -3r Combine like terms: -2r + -3r = -5r 16 + -5r = 11 + 3r + -3r Combine like terms: 3r + -3r = 0 16 + -5r = 11 + 0 16 + -5r = 11 Add '-16' to each side of the equation. 16 + -16 + -5r = 11 + -16 Combine like terms: 16 + -16 = 0 0 + -5r = 11 + -16 -5r = 11 + -16 Combine like terms: 11 + -16 = -5 -5r = -5 Divide each side by '-5'. r = 1 Simplifying r = 1
| 12x=-45 | | 1x-5=3x+4 | | 10(-0.2X-1)=1/2(8X) | | 4(w+9)=4w-36 | | 162r=3r+11 | | p-67.5=24.1 | | 2w+16=6(w+6) | | 36=[4-y]3 | | (xy)^2/5 | | 0.15x^2-0.8x+1=0 | | 4/5×7 | | 5(x-3)=-9x-29 | | 0.5(4-8y)=5-3y | | 8=2x-12y | | 5x-1=x+15 | | 6a+2[a+6]=28 | | 4x+6+2x-10+3x+4=180 | | 27/50=x/100 | | 45A-7B=69 | | 6x+7+4x+23=90 | | 5k^2=-3k | | 8x-6-3x=x+7+x | | 2+3x=3x-8-x | | -16r-3r=36 | | -2(x-3)+6x=2x+3(x-4) | | 16r-3r=36 | | 4*x+5=-1 | | 0.5*x+3=13 | | 16r+3r=36 | | 2(4s+6)=60 | | -5(-3M-16)=-4(0.5M+1) | | 8x=4y-5 |